PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN, KEPERCAYAAN DAN RELIGIUSITAS ISLAMI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MUKENA MELALUI TOKO RAHAYU MUKENA - Rahayu Dwi Lestari; Jaharuddin Jaharuddin (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
ABSTRACTThis study aims to determine whether perceptions of price, service quality, trust, and Islamic religiosity have an influence on online purchasing decisions via Instagram at the Rahayu Mukena store. This research method uses quantitative. The results of the study explain that Perceived Price has a positive and significant effect on Purchasing Decisions. Service Quality has a positive but not significant effect on Purchasing Decisions. Trust has a positive and significant effect on purchasing decisions. Islamic religiosity has a negative but significant effect on purchasing decisions. This research implies that the better the pricing that is applied, the trust given by the Rahayu Mukena Store, and the high one's Islamic religiosity, the more it can increase the purchasing decisions of consumers, especially Rahayu Mukena consumers. The novelty of this research is that it has similarities with previous studies, namely the use of the dependent variable regarding purchasing decisions, although, for the independent variables, each only uses a portion of the independent variables that I studied. Apart from that, in this study, there are also differences, namely in the use of data analysis methods used, as well as the fundamental differences between my research and previous studies, namely differences in research objects and observation periods between the two. Keywords : Perceived   Price,   Service  Quality,  Trust,  Islamic Religiosity, and Purchase Decision